A study on the adequacy of the law governing the control of sale, supply and prescribing of psychotropic substances in Malaysia / Mohammad Faizal Ahmat Zainuri - Ahmat Zainuri, Mohammad Faizal (2016)
A report from INCB which was release in 2nd March 2005 stating Malaysia was among the highest importer of psychotropic substance in the world. Psychotropic substance misuse has trigger the PSD regarding the adequacy of the legislation in control of sale, supply and prescribing of psychotropic substance. However, current law in Malaysia is not enough to prevent the misuse of psychotropic substance. A lot of problems arise due to lack of provisions regarding quotas, prescribing following clinical practice guidelines which currently not available in Malaysia (not legally binding at the moment), and lack of provision regarding misuse of psychotropic substance. Problems regarding misuse of psychotropic substance can be effectively addressed by carefully examining the strength and weakness of current law in order to identify the gaps that need to be filled. This research proposal will identify and analyse the current law in Malaysia and also other countries law (UK, US, Australia and India) regarding control of sale, supply and prescribing of psychotropic substance. It is hope the study can contribute to successfully treating patients using psychotropic substances rationally. In conclusion, this research proposal says that there should be amendments to the current law to prevent the misuse of psychotropic substance.